2010
DOI: 10.1088/0022-3727/43/36/365402
|View full text |Cite
|
Sign up to set email alerts
|

A study of the glass transition in the amorphous interlamellar phase of highly crystallized poly(ethylene terephthalate)

Abstract: Poly(ethylene terephthalate) (PET) is a semi-crystalline polymer that can be crystallized up to different degrees heating from the amorphous state. Even when primary crystallization has been completed, secondary crystallization can take place with further annealing and modify the characteristics of the amorphous interlamellar phase. In this work we study the glass transition of highly crystallized PET and in which way it is modified by secondary crystallization. Amorphous PET samples were annealed for 4 hours … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…It has been found that the dielectric strength and the width of the relaxation time distribution are sensible to the processing parameters but molecular coupling does not change significantly with the blend composition or the degree of transesterification [4]. The α relaxation, the dielectric manifestation of the glass transition [5], depends strongly on the thermal history [6] because crystallization and physical aging affects the amorphous phase that is where this phenomenon takes place [7]. The relative content of PET and PEN also affects the α relaxation.…”
Section: T-e-t + N-e-n ⇀ ↽ T-e-n + N-e-tmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the dielectric strength and the width of the relaxation time distribution are sensible to the processing parameters but molecular coupling does not change significantly with the blend composition or the degree of transesterification [4]. The α relaxation, the dielectric manifestation of the glass transition [5], depends strongly on the thermal history [6] because crystallization and physical aging affects the amorphous phase that is where this phenomenon takes place [7]. The relative content of PET and PEN also affects the α relaxation.…”
Section: T-e-t + N-e-n ⇀ ↽ T-e-n + N-e-tmentioning
confidence: 99%
“…The cristallinity degree was estimated from differential scan calorimetry (DSC) measurements and found to be less than 10% in all cases. Also, it should be noted that a small degree of crystallinity poses no problem since the α relaxation of the interspherulitic amorphous phase is analogous to the α relaxation of the amorphous material and is easy to distinguish from the α relaxation of the amorphous interlamellar phase (α c ) [7].…”
Section: Experimental 21 Preparationmentioning
confidence: 99%
“…Poly(ethylene terephthalate) (PET) is one of the most important engineering plastics, which has been widely used as a raw material in the manufacture of fibers, packaging, optical devices, and appliances due to its excellent film‐forming property, weather resistance, and transparency (amorphous PET) 1 . The processing of PET involved many physical transformation, such as glass transition, 2,3 crystallization, 4–6 recrystallization, 7,8 double melting 9 and so on. These physical transformation will have effects on the dimensional stability (bending, creeping, softening and so on) and mechanical properties on the resultant PET products.…”
Section: Introductionmentioning
confidence: 99%
“…The results of different dielectric property measurements of PET materials of various structures can be found in the literature . Some of the optical characteristics of PET materials have been reported in literature .…”
Section: Introductionmentioning
confidence: 99%
“…The results of different dielectric property measurements of PET materials of various structures can be found in the literature. [11][12][13][14] Some of the optical characteristics of PET materials have been reported in literature. 15,16 However, the relation between the optical characteristics of the PET track membrane and the temperature has been studied very little.…”
Section: Introductionmentioning
confidence: 99%